Utilization of flywheel energy accumulation for electric traction - Opava, Jaroslav (Univerzita Pardubice, 2006)
Theoretic study is dedicated to the question of the using of the flywheel accumulation systém for the power supply of a traction vehicle. The new knowledges in the branch of construction materials, of electronic regulating convertors and of electric machines allow today to design the high-speed flywheel units. These devices have a high power and energy mass density. The study presents the research methodology for solution of the given question. Herewith it proves the possibility for the practic application of this mobil energy source as the only alone on the traction vehicle.
Použití setrvačníkové akumulace energie pro elektrickou trakci
Keywords: gyroelektrické akumulační systémy; kolejová trakční vozidla; elektrická trakční vozidla; napájení